Anti-quorum sensing activity of spice oil nanoemulsions against food borne pathogens. (March 2016) - Venkadesaperumal, Gopu; Rucha, Sambrey; Sundar, Kothandapani; Shetty, Prathapkumar Halady
Abstract: Quorum sensing (QS) mechanism plays a vital role in many bacterial species, which is found to be implicated in various factors including bacterial pathogenicity and food spoilage. Therefore interrupting the QS mechanism may be an attractive strategy to develop novel QS-based anti-bacterial drugs. Here, we investigated the quorum sensing inhibitory activity of spice oil nanoemulsions (NE) and its antibiofilm property against selected food pathogens using the biosensor strain Chromobacterium violaceum CV026. Essential oil nanoemulsions were formulated by ultrasonic emulsification of Tween80 and water. The emulsification method for nanoformulations was standardized with Tween80 concentration and sonication time to attain high physical solidity and minimum droplet diameter. Stable cumin ( Cuminum cyminum ), pepper (Piper nigrum), and fennel (Foeniculum vulgare) oil nanoemulsions with respective droplet diameters of 52.89 nm, 82.08 nm and 59.52 nm were formulated by ultrasonic emulsification. Nanoemulsions at all tested concentrations inhibited the production of violacein pigment in C. violaceum CV026 below their minimum inhibitory concentration (MIC) level. In addition, the upshot of the current investigation reveals that all three nanoemulsions strongly interferes with quorum regulated phenotypes like biofilm formation and exopolysaccharide (EPS) production. Above findings lay a solid foundation for the utilization of nanoemulsions as QS-based antibacterial/anti-biofilm agents to manage food borne pathogens and biofilm formation in food industries. Highlights: Nanoemulsions were formulated using essential oils of spices to screen its anti-QS activity. QSI activity of nanoemulsions were assessed against food borne pathogens and a bio-sensor. QSI activity was demonstrated using in-vitro techniques like biofilm formation & EPS production. Formulations efficiently inhibited biofilm formation & EPS production of test pathogens. Spice oil nanoemulsion can act as efficient QS-based antibacterial/anti-biofilm agents.